Resposta :
Resposta: 16x
Explicação passo-a-passo: A= 6x / B= -4x / C= 6x
6x-(-4x)+6x
=6x+4x+6x
=16x
![Ver imagem CINTHIAAMORZINHO7](https://pt-static.z-dn.net/files/d33/0213412b9ea573740f7768091909e86e.jpg)
Resposta:
Seria a letra b.
Explicação passo-a-passo:
2x-x+5x
x+5x
6x
4x-6x-2x
-2x -2x
-4x
8x-3x+x
5x+x
6x
A - B + C = 6x -(-4) +6x
16x.
Resposta: 16x
Explicação passo-a-passo: A= 6x / B= -4x / C= 6x
6x-(-4x)+6x
=6x+4x+6x
=16x
Resposta:
Seria a letra b.
Explicação passo-a-passo:
2x-x+5x
x+5x
6x
4x-6x-2x
-2x -2x
-4x
8x-3x+x
5x+x
6x
A - B + C = 6x -(-4) +6x
16x.